2020
DOI: 10.1017/s0030605319001352
|View full text |Cite
|
Sign up to set email alerts
|

Mammals of the Bhagirathi basin, Western Himalaya: understanding distribution along spatial gradients of habitats and disturbances

Abstract: Understanding the distribution of wildlife species and their response to diverse anthropogenic pressures is important for conservation planning and management of wildlife space in human-dominated landscapes. Assessments of anthropogenic impacts on mammals of the Indian Himalayan Region have mostly been limited to locations inside protected areas. We studied the occurrence of mammals in an unexplored landscape, the 7,586 km2 Bhagirathi basin, at an altitude of 500–5,200 m. The basin encompasses wilderness areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The density of Himalayan musk deer was higher in summer (0.4 ± SE 0.1 individuals/km 2 ) than winter (0.1 ± SE 0.05 individuals/km 2 ). The analysis of seasonal habitat use in the study area also showed a trend of decline in captures at high elevations (Pal et al, 2020) in winter, possibly because musk deer migrate to lower altitudes during periods of heavy snowfall. Similar seasonal movements were also observed in other areas (Anwar & Minhas, 2008; Dendup & Lham, 2018).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The density of Himalayan musk deer was higher in summer (0.4 ± SE 0.1 individuals/km 2 ) than winter (0.1 ± SE 0.05 individuals/km 2 ). The analysis of seasonal habitat use in the study area also showed a trend of decline in captures at high elevations (Pal et al, 2020) in winter, possibly because musk deer migrate to lower altitudes during periods of heavy snowfall. Similar seasonal movements were also observed in other areas (Anwar & Minhas, 2008; Dendup & Lham, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, Nilang valley is affected by anthropogenic disturbances such as hunting (Bhardwaj et al, 2010), livestock grazing (Chandola, 2009; RP pers. obs., 2017) and presence of free-ranging dogs (Pal et al, 2020). The differences could also be caused by different survey techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the naïve occupancy of each species was calculated as the total number of camera trap locations of a particular species detected divided by the total number of camera trap stations surveyed [ 42 ]. The estimates of the naïve occupancy and capture rates for the species with four or less photo captures were not compared and kept only in the enumeration table [ 43 ]. Further the difference in the Shannon’s diversity indices between PA and Non-PA was tested using the Hutcheson’s test [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection rates for arboreal mammals was defined as the ratio of independent events to the number of trap days, which is the number of 24 hour periods from camera placement until the battery ran out or the camera was retrieved, and multiplied by 100 (Rovero & Marshall, 2009). We adopted the camera trap detection rate as a mean to estimate relative abundance of arboreal mammal species (Rovero & Marshall, 2009;Pal et al, 2020). All analyses were run in R v. 3.6.3 environment (R Core Team, 2020).…”
Section: Arboreal Camera Trappingmentioning
confidence: 99%